Age at Menarche and Cardiometabolic Health: A Sibling Analysis in the Scottish Family Health Study. Issue 4 (10th February 2018) - Magnus, Maria C.; Lawlor, Debbie A.; Iliodromiti, Stamatina; Padmanabhan, Sandosh; Nelson, Scott M.; Fraser, Abigail
Abstract : Background: Previous studies of age at menarche and cardiometabolic health report conflicting findings, and only a few could account for childhood characteristics. We aimed to estimate the associations of age at menarche with cardiovascular risk factors in unrelated women and within sister groups, under the assumption that within‐sibship estimates will be better adjusted for shared genetics and early life environment. Methods and Results: Our study included 7770 women, from 5984 sibships, participating in the GS:SFHS (Generation Scotland: Scottish Family Health Study). We used fixed‐ and between‐effects linear regression to estimate the associations within sister groups and between unrelated individuals, respectively. Within sibships, the mean difference between sisters with early menarche (≤11 years) and sisters with menarche at 12 to 13 years was 1.73 mm Hg (95% confidence interval [CI], −0.41 to 3.86) for systolic blood pressure, 1.26 mm Hg (95% CI, −0.02 to 2.55) for diastolic blood pressure, −0.06 nmol/L (95% CI, −0.11 to −0.02) for high‐density lipoprotein, 0.20 nmol/L (95% CI, 0.08–0.32) for non–high‐density lipoprotein, −0.34% (95% CI, −1.98 to 1.30) for glucose, 1.60 kg/m 2 (95% CI, 0.92–2.28) for body mass index, and 2.75 cm (95% CI, 1.06–4.44) for waist circumference. There was weak evidence of associations between later menarche (14–15 or ≥16 years) and lower body mass index, waist circumference, and blood pressure. We found no strong evidence that estimates from within‐ and between‐sibship analyses differed (all P values >0.1). The associations with other cardiovascular risk factors were attenuated after adjustment for adult body mass index. Conclusions: Our results suggest that confounding by shared familial characteristics is unlikely to be a major driver of the association between early menarche and adverse cardiometabolic health but do not exclude confounding by individual‐level characteristics.